2011
DOI: 10.1366/10-06197
|View full text |Cite
|
Sign up to set email alerts
|

Chemometric Study on the Forensic Discrimination of Soil Types Using Their Infrared Spectral Characteristics

Abstract: 14Soil has been utilized in criminal investigations for some time because of its prevalence and 15 transferability. It is usually the physical characteristics that are studied, however the research

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…We used variable importance in project (VIP) scores to identify the features that were most important for characterizing each soil type. We defined VIP scores ≥1 as indicative of particularly important features for the model 17 . Among the 66 features selected by GA, there were 28, 30, 29, 32 and 28 with VIP scores ≥1 (solid points in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used variable importance in project (VIP) scores to identify the features that were most important for characterizing each soil type. We defined VIP scores ≥1 as indicative of particularly important features for the model 17 . Among the 66 features selected by GA, there were 28, 30, 29, 32 and 28 with VIP scores ≥1 (solid points in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the method of maximum distance we used to classify individual samples is straightforward and easily implemented, other methods such as centroids or Mahalanobis distances between soil types might lead to improvements in classification accuracy. Alternative methods, such as nonlinear iterative partial least squares followed by linear discriminant analysis (NIPALS-LDA), may also perform better 17 . Data mining should always be explored to improve the accuracy and predictive models for soil type recognition, especially if more spectral data are available for the continued development across larger spatial scales.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its implementation in the field and laboratory offers the possibility of repeating measurements and estimating the ranges of various soil properties such as OM content, texture and CaCO 3 (Lagacherie et al 2008, Liu et al 2017. Several research studies have confirmed the high potentiality of the VIS-NIR spectroscopy to determine and discriminate between soil profiles and to provide information about the influence of soil properties on soil reflectance (Zeng et al 2016, andBaron et al 2011) but at present, few or even no, confirmatory studies have been conducted to discriminate between topsoils of different soil types using the data of the VIS-NIR spectroscopy acquired in the field.…”
Section: Introductionmentioning
confidence: 99%